Effect of graphene addition on microstructure and wear behaviour of the A356-based composite fabricated by thixoforming process - Omar, Mohd Zaidi; Salleh, Mohd Shukor; Wakhi Anuar, Nur Farah Bazilah; W. Zamr, Wan Fathul Hakim; Md Ali, Afifah (Elsevier Editora Ltda, 2024)
Employing graphene as reinforcement in an aluminium matrix is a viable approach for developing composites with exceptional mechanical properties and wear resistance owing to its two-dimensional structure and high strengthening efficiency. This study aims to investigate the microstructure and wear behaviour of A356 aluminium matrix composites reinforced with different graphene nanoplatelets (GNPs) amounts (0.3, 0.5 and 1.0 wt%). The feedstock of composites underwent stir casting before being subjected to the thixoforming process. Field emission scanning electron microscopy (FESEM) and transmission electron microscopy micrographs (TEM) demonstrated the microstructure transformation of the composites after fabrication and the presence of carbon elements in the A356 matrix composite, respectively. TEM micrographs also displayed the existence of aluminium carbide (Al4C3) compound in the composites due to the reaction of aluminium matrix and graphene during fabrication. The hardness testing results revealed the hardness of the composite with 0.3 wt% GNPs is higher than that of A356 alloy by showing an improvement of 51.4% after the thixoforming process. The wear resistance of the composites was enhanced by decreasing the wear rate. In comparison with the as-cast and thixoformed A356 alloys, the thixoformed composite reinforced with 0.3 wt% GNPs exhibited the lowest wear rate, demonstrating a reduction of 18.7% and 11.5%, respectively. These findings demonstrated the significance of GNPs as an effective self-lubricating and favourable reinforcement for A356 aluminium matrix composite in the automotive industry.